2012
DOI: 10.1371/journal.pone.0041560
|View full text |Cite
|
Sign up to set email alerts
|

Widening Educational Disparities in Premature Death Rates in Twenty Six States in the United States, 1993–2007

Abstract: BackgroundEliminating socioeconomic disparities in health is an overarching goal of the U.S. Healthy People decennial initiatives. We present recent trends in mortality by education among working-aged populations.Methods and FindingsAge-standardized death rates and their average annual percent change for all-cause and five major causes (cancer, heart disease, stroke, diabetes, and accidents) were calculated from 1993 through 2007 for individuals aged 25–64 years by educational attainment as a marker of socioec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 23 publications
(18 reference statements)
1
11
0
Order By: Relevance
“…Similar findings have been observed in other US studies 8 10. In an international comparison study in Europe, increased mortality rates among those with low education were found in Lithuania and Estonia between the 1990s and 2000s 11.…”
Section: Discussionsupporting
confidence: 90%
“…Similar findings have been observed in other US studies 8 10. In an international comparison study in Europe, increased mortality rates among those with low education were found in Lithuania and Estonia between the 1990s and 2000s 11.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the higher rates in the urban areas also could be partly attributed to improved diagnoses. A previous study shows that education predicted greater screening frequency, as the colorectal cancer screening rate is higher in college graduates than in those with less than a high school education (Ma et al, 2012). People living in rural areas have a lower education level and were less likely to have ever received any type of screening Characteristics andPredictions in China, 1991-2011 for colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Individual-level studies consistently showed that life expectancy increased markedly for high-SES individuals but increased very little or decreased slightly for low-SES individuals (34,43,47,59). Studies comparing rich and poor counties and census tracts in the United States also showed increasing mortality ratios in the late twentieth century (24,53,54).…”
Section: Empirical Evidence On the Effects Of Income Inequalitymentioning
confidence: 97%